HAMBATAN GURU DALAM PEMBELAJARAN GEOGRAFI MATERI LANGKAH-LANGKAH PENELITIAN GEOGRAFI DI SMAN 12 PADANG - rahmi ulfa fajrina; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to describe the obstacle experienced by teachers in learning geography on the material of geography research steps at SMAN 12 Padang. This research is a qualitative descriptive study. Informants in this study were the geography teachers of class X and the supporting informants were students of class X SMAN 12 Padang. Data collection methods used in the form of interviews, observation and documentation. The results of the study revealed that : (a) Geography teachers already understood the subject matter of geography research steps, but the material wa less effective due to various obstacles in teaching the material. (b)Obstacles experienced by teachers are limited lesson hours that are not proportional to the wide and complex coverage of material, the state of the covid-19 pandemic, less effective material being taught in class X. (c) Efforts made by teachers are to use learning methods that are in accordance with subject matter, utilizing diserve learning resources, guiding in dept student who have difficulty understanding the subject matter.